Advancement of cancer immunotherapy using nanoparticles-based nanomedicine. (November 2022) - Gowd, Vemana; Ahmad, Anas; Tarique, Mohammad; Suhail, Mohd; Zughaibi, Torki A.; Tabrez, Shams; Khan, Rehan
Abstract: Cancer has complex pathophysiology and is one of the primary causes of death and morbidity across the world. Chemotherapy, targeted therapy, radiation therapy, and immunotherapy are examples of traditional cancer treatments. However, these conventional treatment regimens have many drawbacks, such as lack of selectivity, non-targeted cytotoxicity, insufficient drug delivery at tumor sites, and multi-drug resistance, leading to less potent/ineffective cancer treatment. Due to its immanent biophysical property and ability to change in numerous ways, nano-technology has completely transformed how cancer is identified and treated in recent years. Furthermore, nanotechnology providing solutions to these restrictions and boosting cancer therapy. Nanoparticles are widely used nanomedicine platform in cancer immunotherapy due to their excellent physicochemical properties that include size, shape, and surface features, resulting into desirable biological interactions and have been categorized into several types. Nanoparticles can also be potentially be up taken by antigen-presenting cells that promote the cytosolic delivery of encapsulated antigens and adjuvants. Furthermore, nanoparticles can be fine-tuned and functionalized with specific moieties to promote their efficacy in targeting and delivering cargo materials to specific locations. In this review, we summarized and discussed nanoparticles and potential features to be used as carriers in cancer immunotherapy, the current status of different types of nanoparticles, and the importance of their functionalization. Furthermore, we have also discussed nanoparticles-based nanomedicine in targeted delivery of encapsulated cancer immunotherapeutic and their involvement in the modulation of the tumor microenvironment, promoting cancer immunotherapy.